2022
DOI: 10.1126/science.abm8642
|View full text |Cite
|
Sign up to set email alerts
|

Emergent ferroelectricity in subnanometer binary oxide films on silicon

Abstract: The critical size limit of voltage-switchable electric dipoles has extensive implications for energy-efficient electronics, underlying the importance of ferroelectric order stabilized at reduced dimensionality. We report on the thickness-dependent antiferroelectric-to-ferroelectric phase transition in zirconium dioxide (ZrO 2 ) thin films on silicon. The emergent ferroelectricity and hysteretic polarization switching in ultrathin ZrO 2 , conventionally a paraelec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(82 citation statements)
references
References 131 publications
1
80
0
1
Order By: Relevance
“…In 2020, it was suggested that the robust ferroelectricity of (Hf,Zr)O 2 can be retained even when the film thickness decreases to 1 or 1.5 nm, and it was further suggested that unit‐cell‐scale information storage would theoretically be possible because of the flat phonon band of ferroelectric HfO 2 31,32 . Moreover, it has been experimentally demonstrated that ferroelectricity in fluorite‐structured ferroelectric could be retained below 5 Å or even at a single atomic layer 33,34 . Recently, freestanding fluorite‐structured ferroelectrics for flexible devices have also been reported with robust ferroelectricity 35,36 .…”
Section: Advantages and Challenges Of Fluorite‐structured Ferroelectr...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2020, it was suggested that the robust ferroelectricity of (Hf,Zr)O 2 can be retained even when the film thickness decreases to 1 or 1.5 nm, and it was further suggested that unit‐cell‐scale information storage would theoretically be possible because of the flat phonon band of ferroelectric HfO 2 31,32 . Moreover, it has been experimentally demonstrated that ferroelectricity in fluorite‐structured ferroelectric could be retained below 5 Å or even at a single atomic layer 33,34 . Recently, freestanding fluorite‐structured ferroelectrics for flexible devices have also been reported with robust ferroelectricity 35,36 .…”
Section: Advantages and Challenges Of Fluorite‐structured Ferroelectr...mentioning
confidence: 99%
“…31,32 Moreover, it has been experimentally demonstrated that ferroelectricity in fluoritestructured ferroelectric could be retained below 5 Å or even at a single atomic layer. 33,34 Recently, freestanding fluorite-structured ferroelectrics for flexible devices have also been reported with robust ferroelectricity. 35,36 These achievements demonstrated the intrinsic advantage of fluorite-structured ferroelectrics for nano-electronic devices, which are the basic building blocks for neuromorphic computing.…”
Section: Advantages and Challenges Of Fluorite-structured Ferroelectr...mentioning
confidence: 99%
“…Expanding this strategy to FE oxides would provide opportunities, for example, to add nonvolatile functionality or develop neuromorphic devices [190]. In this regard, binary oxides with fluorite structure are promising candidates for such applications: polycrystalline films of Hf 0.8 Zr 0.2 O 2 and ZrO 2 grown by atomic-layer deposition on silicon display FE behavior down to just a single unit cell [191,192]; however, interface optimization, as well as integration of single crystal films may motivate researchers to expand the epitaxial lift-off techniques to fluorite based compounds.…”
Section: Cmos and Flexible Integrated Devicesmentioning
confidence: 99%
“…Ferroelectrics based on hafnia, such as doped HfO 2 and Hf 0.5 Zr 0.5 O 2 , are quite unusual compared with conventional perovskite ferroelectrics. First of all, though these oxides consist of mixed ionic-covalent bonding, it is unclear whether the covalence should play any role in the ferroelectricity. On the other hand, in perovskite oxide ferroelectrics, the existence of orbital hybridization and covalent bonding is important for the ferroelectric distortion .…”
Section: Introductionmentioning
confidence: 99%